Students' critical thinking skills (2011-2020): A bibliometric analysis - Iwan, Iwan; Sumitro, Sutiman Bambang; Ibrohim, Ibrohim; Rohman, Fatchur (Univeritas Papua, 2023)
The purpose of this study is to identify and analyze articles that examine students' critical thinking abilities that have been published in several reputable international journals published in period 2011-2020 using bibliometric analysis. The research was conducted using a systematic mapping method in 4 stages: (1) searching articles using the Publish or Perish (PoP) application in the Scopus database, (2) classifying articles for bibliometric analysis, (3) checking and filling in article metadata and (4) conducting bibliometric analysis using the VOSviewer application. The results of the bibliometric analysis yielded 5 findings, as follows: (1) the trend of publication of critical thinking skills has fluctuated from 2011-2020; (2) the ten most contributing journals have published 46 articles up to 2020; (3) the ten most cited articles resulted in 669 citations; (4) The four highest order keywords that are most widely used in critical thinking skills articles are critical thinking abilities, thinking abilities and students; (5) There are 6 writers who research critical thinking skills the most but have not seen collaboration between the 6 writers; It can be concluded that student critical thinking abilities in the world of education are being researched even though they have fluctuated over the last 10 years.